Monocyte Recruitment by HLA IgG‐Activated Endothelium: The Relationship Between IgG Subclass and FcγRIIa Polymorphisms. Issue 6 (3rd February 2015) - Valenzuela, N. M.; Trinh, K. R.; Mulder, A.; Morrison, S. L.; Reed, E. F.
<x xml:space="preserve">Abstract</x> It is currently unclear which donor specific HLA antibodies confer the highest risk of antibody‐mediated rejection (AMR) and allograft loss. In this study, we hypothesized that two distinct features (HLA IgG subclass and Fcγ receptor [FcγR] polymorphisms) which vary from patient to patient, influence the process of monocyte trafficking to and macrophage accumulation in the allograft during AMR in an interrelated fashion. Here, we investigated the contribution of human IgG subclass and FcγR polymorphisms in monocyte recruitment in vitro by primary human aortic endothelium activated with chimeric anti‐HLA I human IgG1 and IgG2. Both subclasses triggered monocyte adhesion to endothelial cells, via a two‐step process. First, HLA I crosslinking by antibodies stimulated upregulation of P‐selectin on endothelium irrespective of IgG subclass. P‐selectin‐induced monocyte adhesion was enhanced by secondary interactions of IgG with FcγRs, which was highly dependent upon subclass. IgG1 was more potent than IgG2 through differential engagement of FcγRs. Monocytes homozygous for FcγRIIa‐H131 adhered more readily to HLA antibody‐activated endothelium compared with FcγRIIa‐R131 homozygous. Finally, direct modification of HLA I antibodies with immunomodulatory enzymes EndoS and IdeS dampened recruitment by eliminating antibody‐FcγR binding, an approach that may have clinical utility in reducing AMR and other forms of antibody‐induced inflammation.